Neurospora Chronology 1843-2002 - D D Perkins; R H Davis (Fungal Genetics Reports, 2002)
Our recent review included a timeline showing 30 significant events in the history of Neurospora (Davis and Perkins 2002, Nature Reviews Genetics 3:397-403). Many important contributions could not be included in that brief chronology because of space limitations. We present here a somewhat more complete and better documented list of noteworthy developments.